2021
DOI: 10.3390/vaccines9080927
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Hesitancy to mRNA and Viral Vector COVID-19 Vaccines among College Students in Italy

Abstract: Vaccine hesitancy (VH) may be significant in jeopardizing efforts to mass containment of COVID-19. A cross-sectional survey was carried out on a sample of 2667 Italian college students, before the COVID-19 vaccines became available for this age group (from 7 May to 31 May 2021). An online survey was created to obtain information about socio-demographic, health-related, and psychological factors linked to mRNA and viral vector COVID-19 vaccines. Statistically significant higher VH (30.4%) and vaccine resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 42 publications
1
33
1
Order By: Relevance
“…Compared to the general population, older adults may have a higher vaccination intention [ 37 , 38 ], as the COVID-19 vaccination rate among the general population aged 18 years and older ranged from 60.4% to 83.8% [ 34 , 39 , 40 , 41 ]. We also found that among the elderly population willing to be vaccinated, more people preferred to use domestic vaccines, coinciding with a previous study that suggested that 64.2% of the surveyed population preferred to use domestic vaccines [ 42 , 43 ]. The higher willingness to vaccinate among the elderly in this study may be due to the following reasons: first, the clinical trials for the vaccine are more complete at this stage, and its safety and reliability are guaranteed; second, the elderly population may be more willing to receive a vaccination due to their susceptibility and the threat of comorbidities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compared to the general population, older adults may have a higher vaccination intention [ 37 , 38 ], as the COVID-19 vaccination rate among the general population aged 18 years and older ranged from 60.4% to 83.8% [ 34 , 39 , 40 , 41 ]. We also found that among the elderly population willing to be vaccinated, more people preferred to use domestic vaccines, coinciding with a previous study that suggested that 64.2% of the surveyed population preferred to use domestic vaccines [ 42 , 43 ]. The higher willingness to vaccinate among the elderly in this study may be due to the following reasons: first, the clinical trials for the vaccine are more complete at this stage, and its safety and reliability are guaranteed; second, the elderly population may be more willing to receive a vaccination due to their susceptibility and the threat of comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…A more objective assessment indicator could be considered subsequently to explore the vaccination willingness and its influencing factors in a nationally representative group of older adults. Thirdly, the acceptability might vary with different types of COVID-19 vaccines, and our study did not differentiate between the different types of COVID-19 vaccines [ 43 ]. The willingness to vaccinate against different types of COVID-19 vaccines is worth further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine hesitancy was evaluated with two questions (one for the Pfizer-BioNTech vaccine and one for the AstraZeneca vaccine) adapted from a previous study [ 39 ]. Participants were asked to rate their intentions to be vaccinated (“ Several COVID-19 vaccines are currently available.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, since previous studies [ 39 ] showed that VH is higher for viral vector (e.g., the AstraZeneca vaccine) than mRNA (e.g., the Pfizer-BioNTech vaccine) COVID-19 vaccines, and that factors related to viral vector VH were partially different from those related to mRNA VH, in the current study we examine VH separately for Pfizer-BioNTech and AstraZeneca vaccines. It has been hypothesized that the relationships between ECs, BPNs, attitudes toward COVID-19 vaccines and VH should be stronger for the AstraZeneca vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges in the fight against the COVID-19 pandemic is encouraging young adults to take the vaccine to increase the chances of populations achieving herd immunity [3,4]. To date, a number of motivational barriers to vaccination against COVID-19 have been identified among young people, including belief in conspiracy theories [18] and a lack of confidence in the safety, authenticity and efficacy of vaccination [19,20]. Young adults are less concerned about COVID-19 than older adults [21,22], as this disease does not pose a great risk to young adults' health [23].…”
Section: Introductionmentioning
confidence: 99%